PERANCANGAN ROBOT BERODA DENGAN SISTEM KENDALI BERBASIS IOT DAN GUI MENGGUNAKAN SMARTPHONE ANDROID - Dony Hidayat Al-Janan; Gangsar Fadhil Muhammad (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
A Wheeled Mobile Robot (WMR) is a robot that is often used for transporting a good in the industry. This study was conducted to integrate WMR with the Internet of Things (IoT) to control robots remotely, whereas wheeled robots with a DC motor driving power. Graphical User Interface (GUI) is applied for controlling this device via an Android smartphone. As a result; the robot can be driven via GUI commands with a forward speed = 0.535 m/s; reverse speed = 0.4 m/s; right-hand rotation speed = 25.2 rpm; left-hand rotation speed = 23.4 rpm. These robot performances are strongly influenced by the design, construction of the robot, the load received by the driving motor, and the capacity of the driving motor.